Impact of Transformational Leadership on Employee Motivation and Job Satisfaction in Public Sector Organizations in United Kingdom - Elizabeth, Lucy (Human Resource and Leadership Journal, 2026)
Purpose: The purpose of this article was to analyze the impact of transformational leadership on employee motivation and job satisfaction in public sector organizations in United Kingdom. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The impact of transformational leadership on employee motivation and job satisfaction in public sector organizations in the United Kingdom has been largely positive, with transformational leaders fostering higher levels of employee engagement and commitment. Studies have shown that leadership behaviors such as inspirational motivation and individualized consideration contribute to increased job satisfaction and intrinsic motivation, leading to lower turnover rates. These findings suggest that adopting transformational leadership practices in the public sector can enhance workforce morale and overall organizational performance. Unique Contribution to Theory, Practice and Policy: Transformational leadership theory, self-determination theory & herzberg's two-factor theory may be used to anchor future studies on the impact of transformational leadership on employee motivation and job satisfaction in public sector organizations in United Kingdom. For public sector organizations, it is crucial to implement leadership training programs specifically focused on transformational leadership behaviors such as idealized influence, intellectual stimulation, and individualized consideration. Public sector organizations and governments should incorporate transformational leadership development into public service reform policies to ensure that leadership training becomes a central component of the public sector’s human resources strategy.